Hubungan Konsep Diri dan Kepuasan Kerja dengan Sikap Guru dalam Proses Belajar-Mengajar - Hj. Zahera Sy (Universitas Negeri Malang, 2016)
The main purpose of this correlational study was to test the relationship between teachers' self concept and work satisfaction, and their attitudes toward teaching-learning process. The sample consisted of 102 teachers taken purposively from 8 State Senior High Schools (SMUN) out of 15 State Senior High Schools (SMUN) in Palembang Municipality. The data were collected by questionnaire. It could be concluded that there was a positive correlation between teachers' self concept and work satisfaction, and their attitudes toward learning-teaching process. It was suggested that there be a counseling or other special traetments for teachers with negative self concept